Pemberdayaan Masyarakat Terhadap Kesejahteraan Desa Pada Masyarakat Pasar Wisata Yosomulyo Pelangi, Lampung - Ningrum, Lestari; Dewi, Triana Rosalina; Sukmawati, Aprilia (Jurnal Ilmiah Pariwisata, 2021)
The tourism sector is one source of local revenue. Yosomulyo Pelangi Tourism Market was developed to increase people's income through market tourism performances which is the result of increased and growing community participation. The purpose of the study was to determine the effect of community empowerment on Pasar Payugi Pelangi Tourism on the welfare of Yusomulyo Village. The method used is descriptive correlational method with a quantitative approach. Data was collected by distributing questionnaires. The sampling technique in this study used saturated sampling because the total population was the same as the number of samples, namely 30 traders at the Yosomulyo Pelangi Tourism Market. This is because better community empowerment is able to improve the quality of human resources that are able to add new jobs, improve infrastructure, and encourage communities to open or develop businesses that have an impact on improving village welfare as well. It is hoped that the role of the government is involved in empowering the community of Yosomulyo Village because it can provide various trainings that support, not only tourism but also train community independence through empowerment programs, so that people are able to be independent, and slowly improve their well-being. Keywords: Community Empowerment, Village Welfare, Tourist Market